2016
DOI: 10.1089/cap.2015.0071
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Preschool Disruptive Mood Dysregulation Disorder Symptoms and Neural Reactivity to Monetary Reward During Preadolescence

Abstract: Objective: Reward-processing abnormalities are thought to be a key feature of various psychiatric disorders and may also play a role in disruptive mood dysregulation disorder (DMDD), a new diagnosis in DSM-5. In the current study, we used eventrelated potentials (ERP) sensitive to monetary gains (i.e., the reward positivity [RewP]) and losses (i.e., the N200) to examine associations between symptoms of DMDD during early childhood and later reward processing during preadolescence. Methods: To assess early emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
3
29
0
1
Order By: Relevance
“…The present study joins emerging research linking dimensional assessments of irritability with neurocognitive functioning (Dougherty et al, ; Grabell et al, ; Kessel, Dougherty, et al, ; Kessel, Meyer, et al, ; Li et al, ; Perlman et al, ). We add to extant literature by providing evidence that higher levels of early irritability are associated with response inhibition impairments and enhanced activation of a conflict monitoring circuit during marked negative affect.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The present study joins emerging research linking dimensional assessments of irritability with neurocognitive functioning (Dougherty et al, ; Grabell et al, ; Kessel, Dougherty, et al, ; Kessel, Meyer, et al, ; Li et al, ; Perlman et al, ). We add to extant literature by providing evidence that higher levels of early irritability are associated with response inhibition impairments and enhanced activation of a conflict monitoring circuit during marked negative affect.…”
Section: Discussionsupporting
confidence: 65%
“…In young children, irritability can also manifest as long periods of angry or negative mood (e.g., “stays angry for a long time”; Wakschlag et al, ). While progress has been made in carefully cataloging the full range and characteristics of irritability in very young children (Biedzio and Wakschlag, in press; Wakschlag et al, ; Wakschlag et al, ; Wiggins et al, ), emerging evidence suggests that integrating neurocognitive measures can aid in identifying when a young child's irritability is likely to be associated with adverse long‐term outcomes (Dougherty et al, ; Grabell et al, ; Grabell, Olson, Tardif, Thompson, & Gehring, ; Kessel, Dougherty, et al, ; Kessel, Meyer, et al, ; Li, Grabell, Wakschlag, Huppert, & Perlman, ; Perlman et al, ; Perlman, Luna, Hein, & Huppert, ). For example, interactions between early childhood irritability and neural measures of cognitive control predicted whether children developed internalizing or externalizing symptoms at age 9 (Kessel, Meyer, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unknown whether children with DMDD would respond more like those with SMD or those with ODD, as no studies have been conducted. One recent study suggests that early symptoms of DMDD are predictive of enhanced reward processing during preadolescence (Kessel et al, 2016). However, this is clearly an area for further investigation.…”
Section: Frustration Reward and Non-rewardmentioning
confidence: 99%
“…However, given evidence that symptoms of irritability show moderate stability over time (Leibenluft et al, 2006), it is possible that irritability could also be associated with similar biological correlates at other ages. In addition to the literature on SMD, we have recently shown that persistent irritability in 3-year-old children prospectively predicted enhanced reward sensitivity in middle childhood (Kessel et al, 2016). Taken together, these studies suggest that irritability may be related to increased reactivity, regardless of the valence of the precipitating stimuli.…”
mentioning
confidence: 89%